Examining English textbook prototype development for vocational high school students - Marlin, Sri; Ashadi, Ashadi (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2019)
This article examines the development of an English textbook prototype for vocational high school (VHS) students of the Hotel Accommodation study program. Employing a research and development study design involving several steps of procedure: needs analysis, product development, product validation, product revision, product tryout, and final product development. The results of this research were there units of learning material, in which the content of materials and the topics mostly made related to the hotel fields by covering relevant daily activities and current issues and including various types of activities that cover the four English skills. According to the results of the field-testing, the units designed were eligible to be applied in the instructional process as indicated by the mean scores of the students’ agreement ranging from 4.2 to 5 on 5 to 1 Likert scale. This textbook prototype offers an insight to what English learning materials for Hotel Accommodation Study Program is supposed to be. Thus, it is an alternative model of learning material for teaching English for VHS.